Top managers' career variety and time to the top - Stefan Schmid; Simon Mitterreiter (European Management Review, 2021)
The present paper brings novel insights to career literature, in particular to the field of top managers' careers: first, by relying on the boundaryless career approach, we investigate how those managers who reach the top differ in terms of career variety before being appointed to the board. Second, by combining the boundaryless career approach with human capital theory, we analyze the association between top managers' career variety and the time it takes them to reach a board level position. For our empirical study, we use a sample of top managers from German DAX-30 firms. Our results reveal four distinct clusters of top managers, indicating that, before reaching the management board, no uniform career path exists. We also demonstrate that more career variety does not shorten an individual's way up to upper echelons; rather, it extends the time it takes to ascend to the top.
Keywords: 650; Boundaryless career; career pattern; career variety; executive careers; time to the top; top managers